Effect Of Behavior Leadership And Job Satisfaction To Organization Commitment Through Employee Trust As Variable Mediating In Pt.Bram - Prastiyo Diatmono (Business and Entrepreneurial Review, 2019)
The Problem of this research is organization commitment as a part an important strategy for deciding the follow-up of a strategic plan that is influenced by leadership behavior, job satisfaction through employee trust as a mediating variable in which there is a gap between theoretical and actual. The results obtained by the company that can change its decision in a certain period have an impact on the organization's commitments that have been previously set. The purpose of this research is to know effect of effect of behavior and job satisfaction on organization commitment through trust employee as mediating variable   in PT. BRAM.  The methodology of this research was testing hypothesis. The data used were primary data collected from questionnaire. The samples consisted of 110 employees PT. BRAM, which were determined through purposive sampling method. The data were analyzed through Structural Equation Model (SEM) of PLS 2.0. The finding and contribution in this research that leadership behavior and job satisfaction had a direct effect on employee trust and employee trust had direct effect on organization commitment. Research implication of this research finding            PT. BRAM to make strategies planning with implementation involving good leadership behavior, employee job satisfaction and employee trust as mediating on organization commitment.